Evaluating The Implementation of Deep Learning in Social ‎Studies at Junior High School: ADKAR Model Analysis ‎ - Dicky Noveka Firmanzah; Septina Alrianingrum; Nuansa Bayu Segara (Yayasan Darussalam Bengkulu, 2026)
This study aims to evaluate the implementation of deep learning in Social Studies instruction at junior secondary schools through the ADKAR model, which consists of awareness, desire, knowledge, ability, and reinforcement. A qualitative implementation evaluation design was employed, involving principals, Social Studies teachers, and students from several junior secondary schools in Pasuruan Regency that had participated in deep learning training organized by BBGTK East Java. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing, with data validity ensured through source triangulation, technique triangulation, member checking, and peer debriefing. The findings reveal that teachers have developed awareness of the importance of deep learning and show positive motivation to implement it; however, their knowledge remains largely conceptual, their ability to translate deep learning principles into consistent classroom practices is still developing, and institutional reinforcement through supervision, evaluation, mentoring, and professional learning communities remains insufficient. This study implies that the sustainable implementation of deep learning requires not only initial training but also systematic school-based reinforcement, continuous professional development, and collaborative instructional support to strengthen teachers’ pedagogical transformation in Social Studies learning.